PROSPECTIVE SOLUTION OF TECHNOLOGY OF COMBINATION OF LASER SCANNING OF ARCHAEOLOGICAL MONUMENTS AND GNSS TECHNOLOGIES (Web of Technology: Multidimensional Research Journal, 2024)
This article describes the process of using GNSS technology to survey architectural monuments and open cultural heritage through the simultaneous use of GNSS technology with a ground penetrating radar scanner. Particular attention is paid to processing the data obtained during the scanning process and creating drawings based on them. Attention is paid to obtaining the most objective results about the condition of historical architectural monuments, as well as obtaining detailed drawings to determine the geometric integrity and damage of the object. Review of problems, current state and main trends in the development of archaeological research based on the widespread use of modern geoinformation technologies.